2018
DOI: 10.1177/1074248418808389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet GPIIb/IIIa Receptor Blockade With MK383 on Infarct Size and Myocardial Blood Flow in a Canine Reocclusion Model

Abstract: Platelet activation and aggregation during ischemia influence reperfusion-related myocyte necrosis, myocardial perfusion at the microvascular level, and thereby eventual recovery of cardiac performance. Inhibition of platelet activity therefore represents a worthwhile target to reduce cellular injury. The current study examined the effects of MK383 (tirofiban), a potent inhibitor of platelet aggregation, on infarct size and myocardial perfusion in canine subjects to either reocclusion (ie, 120-minute + 60-minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…6 In a MR CLEAN subgroup analysis, Mulder et al found that prior treatment with oral daily antiplatelet drugs did not increase the occurrence of death, sICH, or other safety concerns, and may instead improve functional outcome. 7 Another study evaluated the relationship of prior aspirin use with early efficacy and safety outcomes in patients with emergent large vessel occlusion (ELVO) treated with MT, and indicated that antiplatelet pre-treatment does not increase the risk of sICH and may independently improve functional independence. 8 However, the peak concentrations and onset rates of oral antiplatelet drugs are low, thus they are not suitable for first aid in AIS.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a MR CLEAN subgroup analysis, Mulder et al found that prior treatment with oral daily antiplatelet drugs did not increase the occurrence of death, sICH, or other safety concerns, and may instead improve functional outcome. 7 Another study evaluated the relationship of prior aspirin use with early efficacy and safety outcomes in patients with emergent large vessel occlusion (ELVO) treated with MT, and indicated that antiplatelet pre-treatment does not increase the risk of sICH and may independently improve functional independence. 8 However, the peak concentrations and onset rates of oral antiplatelet drugs are low, thus they are not suitable for first aid in AIS.…”
Section: Discussionmentioning
confidence: 99%
“…glycoprotein 2b/3a blockers, etc.) have also reported significant anti-necrosis and anti-arrhythmic effects [82,83]; however, cardioprotective efficacy of these agents may be limited with extended ischemic durations [84].…”
Section: Pharmacologic Strategiesmentioning
confidence: 99%
“…Therefore, antiplatelet therapy is indispensable in operation. Studies have shown that tirofiban can effectively improve myocardial perfusion in patients and reduce the incidence of postoperative complications (Kingma, 2019). Tirofiban is a highly effective and reversible GP b/a inhibitor, which can prevent platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%